Puerarin attenuates neurological deficits via Bcl-2/Bax/cleaved caspase-3 and Sirt3/SOD2 apoptotic pathways in subarachnoid hemorrhage mice - Zhang, Yu; Yang, Xue; Ge, Xuhua; Zhang, Fayong (Biomedicine & pharmacotherapy, 2019)
Subarachnoid hemorrhage (SAH) results in many brain dysfunctions and the neuroprotective function of puerarin after brain damage has been demonstrated in several studies. But whether puerarin can reduce brain nerve damage after SAH is not clear.In this study, we hypothesized that puerarin had the neuroprotective effect after SAH, and this protection could be mediated by bothBcl-2/Bax/Cleaved caspase-3 and SIRT3/SOD2 apoptotic signaling pathways. First, we used neurological score, brain water content and so on to detect the neurological deficits after SAH. Then apoptosis neuron rate was detected by TUNEL staining. Western blot was carried out to explore the alteration of Blc-2, Bax, cleaved caspase-3 and Sirt3.Also, ROS acitivity and As-lysine level of SOD2 should be detected with assays. We demonstrate that puerarin attenuated the neurological deficits, effectively relieves cerebral edema, and reduce BBB disruption in SAH mice.And we revealed that a reduced rate of apoptosis neuron has been found out in puerarin treatment after SAH. In addition, obviously higher ratio of Blc-2/Bax and decreased expression of cleaved caspase-3 in puerarin-treated SAH micecomparing with vehicle-treated SAH animals had been found. Furthermore, puerarin effectively reversed these alterations in expression and inhibits ROSproduction induced by SAH. Also, puerarin can increase SOD activation after SAH and protect the expression of Sirt3 after SAH. In coclusion, puerarin can provide potential neuroprotection from the SAH damages, and can be act as a novel therapy for SAH.